Robust Production of Merkel Cell Polyomavirus Oncogene Specific T Cells From Healthy Donors for Adoptive Transfer - Davies, Sarah I.; Barrett, John; Wong, Susan; Chang, Mark Jesse; Muranski, Pawel J.; Brownell, Isaac (Frontiers in Immunology, 2020)
Virus positive Merkel cell carcinoma (VP-MCC) is an aggressive but immunogenic skin malignancy driven by Merkel cell polyomavirus (MCPyV) T antigen (TAg). Since adoptive T cell transfer (ACT) can be effective against virus-driven malignancies, we set out to develop a methodology for generating MCPyV TAg specific T cells. MCPyV is a common, asymptomatic infection and virus-exposed healthy donors represent a potential source of MCPyV TAg specific T cells for ACT. Virus specific T cells were generated using monocyte-derived dendritic cells (moDCs) pulsed with MCPyV TAg peptide libraries and co-cultured with autologous T cells in supplemented with pro-inflammatory and homeostatic cytokines for 14 days. Specific reactivity was observed predominantly within the CD4+ T cell compartment in the cultures generated from 21/46 random healthy donors. Notably, responses were more often seen in donors aged 50 years and older. TAg specific CD4+ T cells specifically secreted Th1 cytokines and upregulated CD137 upon challenge with MCPyV TAg peptide libraries and autologous transduced antigen presenting cells. Expanded T cells from healthy donors recognized epitopes of both TAg splice variants found in VP-MCC tumors, and minimally expressed exhaustion markers. Our data show that MCPyV specific T cells can be expanded from healthy donors using methods appropriate for the manufacture of clinical grade ACT products.